Potential of Biochar for Defluoridation of Drinking Water: A Review - Mwadalu, Riziki; Rutto, Mercy; Abdi, Abey M.; Chappa, Luciana R.; Nungula, Emmanuely Z.; Ngaiza, Victor V.; Raj, Abhishek; Dlamini, Jerry C.; Raza, Muhammad A.; Soratto, Rogério P. [UNESP]; Nasar, Jamal; Gitari, Harun I. (Springer Nature, 2025)
Fluoride is a geogenic contaminant common in drinking water sources globally. It can originate from natural and anthropogenic activities. These sources include weathering of fluoride-bearing parent rocks and application of phosphatic artificial fertilizer. A number of technologies have been developed for defluoridation globally to alleviate effects of accrued high fluoride contamination. This review explores potential of biochar for defluoridation of drinking water. The introduction of this chapter focuses on the magnitude of fluoride contamination globally. Further, the review explores the main sources of fluoridation with emphasis on anthropogenic and natural sources. In addition, effects of fluoridation on human health problems ranging from skeletal to dental fluorosis, which result from consumption of fluoride-contaminated water are highlighted. The metadata analysis also explores the potential of biochar-based defluoridation technologies for treatment of drinking water. Additionally, it highpoints the different technologies available for defluoridation. These technologies include: precipitation, membrane-filtration processes, adsorption, ion-exchange among others. The review also notes that the Nalgonda method is most commonly used in developing countries for defluoridation. The merits and drawbacks of the different defluoridation technologies are also emphasized in the chapter. The chapter equally explores the characteristics of an efficient adsorbent for defluoridation owing to the fact that adsorption is widely used globally. Further, a review of fluoride removal efficiency of different biochars produced from different feedstocks has been discussed. The contribution of biochar-based technologies for fluoride removal can offer cost-effective and environmentally sustainable alternatives for treatment of drinking water globally.
Keywords: Adsorption; Biochar; Fluoride; Fluorosis; Removal efficiency